Las estrategias metodológicas y su incidencia en el desarrollo psicomotriz de las niñas y niños de primer año de educación básica de la unidad educativa pública “Mentor Gamboa Collantes” del cantón Santo Domingo, provincia de Santo Domingo de los Tsáchilas, período lectivo 2013-2014 - Sanmartín Cruz, Mirian Carmen (2014)
This thesis refers to "METHODOLOGICAL STRATEGIES AND THEIR IMPACT ON BASIC EDUCATION FIRST YEAR CHILDREN PSYCHOMOTOR DEVELOPMENT "MENTOR GAMBOA COLLANTES” PUBLIC SCHOOL SANTO DOMINGO CANTON, SANTO DOMINGO Tsáchilas PROVINCE, PERIOD 2013-2014" It was conducted according to the provisions of the Regulation of Academic Board of the Loja National University . As a General Objective: To awareness to teachers abort to the importance of Methodological Strategies for the children Psychomotor Development. of Basic Education first year. The methods used for the preparation of this research work were: Scientist, Inductive- Deductive, Analytic - Synthetic, Descriptive and Statistical Model, which served them help efficiently achieve the goal. The techniques and instruments used were: Survey applied to teachers for Determining Strategies used by teachers in the daily work; and, a Qualitative Test of Psychomotor: applied to children to evaluate the Psychomotor Development. It is concluded that: 67% of teachers surveyed in exchange Methodological Strategies applied in daily work selected recovery strategy; and , 33% design strategy. While 100% of the teachers surveyed think that by Methodological Strategies employed in the working day in the child develops areas: Cognitive, Motor, Psychomotor; and 33% areas: Socio-emotional and language. The results of Qualitative psychomotor test applied children, to assess the Psychomotor Development determines that : in the corresponding test area Body Outline and Time, reflecting a return of 33% vol , 60% in the course of acquisition ; and 7% doesn´t acquired; In the Laterality of 43 %, 53 % by way of acquisition and not acquired 4% ; Balance area acquired 42% , 53 % by way of acquisition, acquired 5%, no; temporomandibular area - Space 48% acquired, 4 % not acquired; in the area of Fine Motor gained 60%, 33 % by way of acquisition, 7% not acquired; and in the area of Gross Motor, reflect an acquired result of 52%, 45% in the course of acquisition; and, 3% not acquired.